2015
DOI: 10.1080/1533290x.2014.946345
|View full text |Cite
|
Sign up to set email alerts
|

Would You Watch It? Creating Effective and Engaging Video Tutorials

Abstract: Video tutorials are a common form of library instruction used with distance learners. This paper combines professional experience and literature reviews from multiple disciplines to provide a contextual overview of recommendations and findings for effective and engaging videos. The tools for tutorials appear in five main categories: screencasts, slidecasts, live action video, animation, and interactivity. Not all tools work for every task or skill level, so it is important to have an understanding of the optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
18
1
5
Order By: Relevance
“…Their preferred video length would have been 5 to7 minutes even though they noted that they themselves would probably not watch an assigned video that was that long. In follow up discussions, 80% of the students indicated that when assigned to watch a video over 5-7 minutes they tended to only watch parts of videos up to about 3 minutes in length which is similar to Martin and Martin (2015) findings. However, our participants stated that they do watch videos that are longer in length if they have a personal motivation to watch.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Their preferred video length would have been 5 to7 minutes even though they noted that they themselves would probably not watch an assigned video that was that long. In follow up discussions, 80% of the students indicated that when assigned to watch a video over 5-7 minutes they tended to only watch parts of videos up to about 3 minutes in length which is similar to Martin and Martin (2015) findings. However, our participants stated that they do watch videos that are longer in length if they have a personal motivation to watch.…”
Section: Resultssupporting
confidence: 75%
“…Video is often used in higher education for instructional and tutorial purposes (Campbell, 2012, Martin & Martin, 2015Shipper, 2013, Yarning & Yit-Liang, 2015Wen-Jung & Cigas, 2013). Teachers assign students to watch videos both in and out of the classroom for the purpose of introducing a topic, watching recorded lectures, encouraging discussions, learning a second language, explaining activities or assignments, and recording screencasts (step by step instructions to complete a procedure or process on a computer).…”
Section: Students As Consumers Of Video In the Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…This assertion is somewhat supported by Chen and Yang (2019), who find that engagement with content extends to 6 min but is highest when the video is less than 3 min. In contrast, Guo et al (2014) found that students stay engaged even during longer videos, between 6-12 min, whereas Martin and Martin (2015) found that, regardless of its length or presence or absence of an introduction, only about a third of the viewers complete a whole video. What must be underscored is that the type of video and the tutorial content vary between these studies, so it is not necessarily the case that these results are contradictory, but rather that the focus is inconsistent.…”
Section: Theoretical Frameworkmentioning
confidence: 86%
“…Recent research has found, though, that information literacy learning in particular can be greatly assisted through digital media such as online courses and instructional videos (Renon, Pychyl, & Motz, 2008;Tewell, 2010;Wyant, 2013). Video has proven to be a particularly effective method of delivering course content, especially when specifically designed for that purpose (Martin & Martin, 2015).…”
Section: Background and Motivationmentioning
confidence: 99%